A Randomized Comparison of the Healing Response Between the Firehawk Stent and the Xience Stent in Patients With ST-Segment Elevation Myocardial Infarction at 6 Months of Follow-Up (TARGET STEMI OCT China Trial): An Optical Coherence Tomography Study - He, Yuan; Wang, Rutao; Liu, Jianzheng; Li, Fei; Li, Jiayi; Li, Chengxiang; Zhou, Jingyu; Zhao, Zhijing; Yang, Wangwei; Mou, Fangjun; Wang, Jing; Kan, Jing; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The healing response of the Firehawk stent in ST-segment elevation myocardial infarction (STEMI) patients remains unclear. Aims: We compared the vascular healing of a biodegradable polymer sirolimus-eluting stent (Firehawk) versus a durable polymer everolimus-eluting stent (Xience) at 6 months after percutaneous coronary intervention in STEMI patients. Methods: In this prospective, multicenter, randomized, noninferiority study, patients within 12 hours of STEMI onset were randomized 1:1 to receive Firehawk or Xience stents. Optical coherence tomography (OCT) follow-up was performed at 6 months after the index procedure and assessed frame by frame. The primary endpoint was the neointimal thickness at 6 months evaluated by OCT. The safety endpoint was target lesion failure (TLF) at 12 months. Results: The Firehawk stent was noninferior to the Xience stent in terms of the neointimal thickness (73.03 ± 33.30 μm versus 78.96 ± 33.29 μm; absolute difference: -5.94 [one-sided 95% lower confidence bound: -23.09]; Pnoninferiority <0.001). No significant difference was observed between the Firehawk and Xience groups regarding the percentage of uncovered struts (0.55 [0.08, 1.32] % versus 0.40 [0.21, 1.19] %, P = 0.804), the percentage of malapposed struts (0.17 [0.00, 1.52] % versus 0.17 [0.00, 0.69] %, P = 0.662), and the healing score (1.56 [0.23, 5.74] versus 2.12 [0.91, 3.81], P = 0.647). At 12 months, one patient in the Firehawk group experienced a clinically indicated target lesion revascularization. No other TLF events occurred in both groups. Independent risk factors of the neointimal thickness included body mass index, hyperlipidemia, B2/C lesions, thrombus G3-5, thrombus aspiration, and postdilation pressure. Conclusions: In patients with STEMI, Firehawk was noninferior to Xience in vascular healing at 6 months. Both stents exhibited nearly complete strut coverage, moderate neointimal formation, and minimal strut malapposition.